Complex Regional Pain Syndrome Type 1 Produced by Hematoma Formation after Blood Donation: A Case Report - Cheng-Chiang Chang; Shin-Tsu Chang (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2021)
The occurrence of hematoma and bruise formation, accounting for the majority of donation-related complications in the arm, rarely results in Complex Regional Pain Syndrome (CRPS). We report a 24-year-old man who presented with CRPS on his right upper limb two months later due to hematoma and bruising formation just after a blood donation following with immediate performance of strenuous exercise in the upper limbs. Triple phase bone scan, one of the bone scintigraphic studies, revealed positive findings and was compatible with the symptoms of CRPS, e.g. hyperalgesia, swelling and discoloration. The potentially disabling condition, however, ended up with a thankfully benign outcome because of our early finding and proper treatment that included three-day oral prednisolone and two-week physiotherapy and occupational rehabilitation. To our knowledge, CRPS produced by donation-related complications with subsequent hematoma and bruise due to vigorous exercise is rare. CRPS should be taken into consideration in a blood donor who demonstrated allodynia because of performing heavy exercise immediately after blood donation.